Uma contribuição para o suporte à estabilidade de frequência no contexto das microrredes por meio de um sistema de armazenamento de energia a batería. - Silva, Mateus Franco (2020)
Concepts such as decentralization, decarbonization, and democratization of electricity use have an impact to increase distributed generation. Due to this growth and mainly concerning about intermittent sources of energy, new paradigms and challenges for distribution systems are proposed, with a highlight towards the microgrids. These reduced structures facilitate the integration of distributed sources, storage systems and local loads, being pointed as fundamental architectures for the advance of the so-called smart grids. In addition, these systems have the versatility to be able to operate either connected to the main grid or on an islanded mode. However, despite the benefits that these architectures present, one must also take into account the particularities of these systems, especially regarding their stability, such as the inherent low inertia of these systems and the transition events between modes of operation. Energy storage systems, especially batteries, have also attracted attention, experiencing a larger picture concerning the market and set of applications. Presenting itself among other possibilities, as promising tools with regard to the challenges mentioned and others concerning the proper operation of the microgrids. In this context, this work analyzes through simulations in Simulink / Matlab environment the contribution that an energy storage system, using lithium-ion technology, can provide the frequency stability of a microgrid in front of a disturbance and successive islanded mode operation. For this, it is used as a test system based on a real microgrid from Ulleungdo Island, South Korea. The obtained results demonstrate the benefits that the battery energy storage system employed can provide by means of droop and synthetic inertia controls, in relation to the deviation and rate of change of frequency of the microgrid before events that cause active power unbalance. Moreover, it is also proposed an improvement about synthetic inertia control over recovery time, a management system for controlling the operation and maintenance of the state of charge of the storage system.